The Minims of Notre Dame: Underpinnings of Sorin's University, 1842-1929 - Casey, Marion T. (American catholic studies, 2016)
The story of the Minims (boys ages 5 through 12) at the University of Notre Dame, 1842-1929, is the story of the coming together of the ambitions of an immigrant French priest and the upwardly mobile Americans who sent their children to study in an isolated part of northern Indiana. Fr. Edward Sorin, CSC, the founder of the university, arranged that these young students would pay the same substantial tuition paid by upper classmen. Not only did this insure the existence of the fledging university, but the Minims set a tone for academics, religion, patriotism, and sports at the institution. In 1917 when Cardinal James Gibbons visited Notre Dame for its 75th anniversary, he declared that while there were many universities which had outstanding campuses this was the only one that had been erected without the help of large donations and is maintained with practically no endowment. Father Sorin's small Minims were a key part of that success.